A COMPARATIVE STUDY OF SPEAKING ABILITY: ENGLISH CAMP PARTICIPANTS AND NON-PARTICIPANTS AT MAN 1 KUANTAN SINGINGI - Aldi Purnomo; Yusrida Yusrida (State Islamic University of Sultan Syarif Kasim Riau, 2026)
This study aimed at finding out significant differences in speaking ability between students participating in English Camp program and those who did not participate in English Camp program at State Islamic Senior High School 1 Kuantan Singingi. It was quantitative study with causal-comparative design. All eleventh-grade students at State Islamic Senior High School 1 Kuantan Singingi were the population of this study, and they were 236 students. 30 students were selected as samples selected by using purposive sampling technique, and they consisted of 15 English Camp participants and 15 non-English Camp participants. The instrument of collecting data was speaking test, and the data were analyzed by using independent sample t-test with the help of SPSS 27. The findings showed that the score of Sig. (2-tailed) was 0.001 lower than 0.05, and it indicated a significant difference in speaking ability between the two groups. Thus, Null hypothesis (H0) which stated that there was no significant difference in speaking ability between students participating in English Camp and non-participants in English Camp was rejected, and Alternative hypothesis (Ha) was accepted.